The fast progressor patient as an emerging clinical entity in patients with coronary atherosclerosis; exploratory study on possible molecular substrates. (14th October 2021) - Garcia Camarero, T; De La Torre Hernandez, J M; Remuzgo-Martinez, S; Lera-Gomez, L; Pulito-Cueto, V; Genre, F; Lopez-Mejias, R; Perez-Fernandez, R; Gonzalez-Gay, M A; Veiga-Fernandez, G; Sainz Laso, F; Lee Hwuang, D H
Abstract: Background: Once coronary atherosclerosis is clinically evident, it presents a very different rate of progression in each particular patient, being this progression one of the most important factors influencing on prognosis. Angiographic progression of lesions has been approached in some studies and certain driving factors have been identified. Nonetheless, clinical progression is more relevant but predictive factors remain less known. Purpose: We aim to characterize a group of patients with accelerated clinical atherosclerosis ("fast progressors", FP) and compare them to a stable group ("long standing stable", LSS) both at baseline conditions, in order to explore potential markers or modulators that might have an impact on the prognosis. Methods: We designed a case and control (1:2) study comparing the FP group (at least 3 different coronary revascularizations over the novo or previously non-significant lesions in a 10-year period of time), to a group of patients with LSS ischemic heart disease (those who have remained clinically stable during at least 10 years after a first coronary revascularization). We have analysed clinical, angiographic, social and environmental factors, as well as molecular substrates, the latter in baseline conditions. Results: We identified 58 cases and compared them to 122 sex and age paired controls. Demographic characteristics and risk factors profile were similar in both groups. Clinical presentation at first event and coronary disease extent was also comparable in between groups. Figure 1 shows serum levels of patients during a stable phase of their disease. Creatinine was higher in the fast progressor group (FP) (p=0.03).Regarding the lipid profile LDLc and Apo B100 levels tended to be lower in the FP group most likely related to a more enhanced statin treatment in these group. Conversely, HDL and Apo A1 level were clearly lower in the FP group which could be explained due to an underlying higher risk condition. As to inflammatory determinants, CRP was found to be similar in both groups but IL-6 was significantly higher in the FP group. This could suggest that IL-6 levels might be a key marker of severity in the FP even at baseline condition. Of note, 10 patients showed IL-6 levels much higher than the mean. Moreover, we also assessed IL-6 genic expression, finding significant higher levels in the long standing stable group (LSS) (Figure 2). These findings suggest that the increase of IL-6 expression observed in the LSS group is not linked to a higher IL-6 production, therefore, the inflammatory state in those patients might be more controlled. Conclusion: The main differential features at baseline of a clinically fast progressor patient compared to a long standing stable might reside in low HDL/Apo A1, along with a higher level of inflammation as estimated by IL-6 levels, but not CRP. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): AMGEN